2011
DOI: 10.1007/s00404-011-2025-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of CA 125, CA 15-3, CA 19-9 and CEA in normal pregnancy: a longitudinal study

Abstract: These findings suggest that maternal serum levels of CA 125, CEA and CA 19-9 were increased during third trimester of pregnancy. However, these elevations were within the normal range. CA 15-3 is independent of gestation and reliable tumor markers in monitoring malignancy in pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 13 publications
5
37
0
3
Order By: Relevance
“…As illustrated in Table 3, CA 15-3 values were described in six publications [6-11], of which two (n = 12 and n = 30) had a longitudinal design [7,11]. Although values largely remained below the cut-off, a significantly increased level was observed during pregnancy in five of the six studies, with the highest levels occurring in the third trimester.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated in Table 3, CA 15-3 values were described in six publications [6-11], of which two (n = 12 and n = 30) had a longitudinal design [7,11]. Although values largely remained below the cut-off, a significantly increased level was observed during pregnancy in five of the six studies, with the highest levels occurring in the third trimester.…”
Section: Resultsmentioning
confidence: 99%
“…Although values largely remained below the cut-off, a significantly increased level was observed during pregnancy in five of the six studies, with the highest levels occurring in the third trimester. In three of the four most recent studies, between 3.3% and 20% of all measurements were found to be above the cut-off value [8-11]. The highest reported CA 15-3 value was 56 U/mL in the third trimester [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The endometrium is a major source of CA125 in healthy women, and it is plausible that the extensive pregnancy-induced changes in the endometrium contribute to long-term changes in circulating CA125 and HE4. Further, data suggest CA125 increases during early pregnancy and close to delivery [3236]; it is plausible that the higher concentrations observed in pregnancy persist post-pregnancy. One study reported higher CA125 concentrations among women reporting parity of two or higher [37], however, an association between parity and CA125 has not consistently been observed among healthy women [7].…”
Section: Discussionmentioning
confidence: 99%
“…One of these tumor markers, CA 19-9, is mostly used as a serum marker for malignancies, but it is also present in the serum and amniotic fluid of pregnant women [20]. In a prospective longitudinal study, serum concentrations of CA 125, CA 15-3, CA 19-9, and CEA were followed in healthy pregnant women throughout pregnancy [21]. No significant difference was observed in serum maternal serum CA 19-9 levels between the first and second trimesters; however, third trimester CA 19-9 levels showed www.…”
Section: Discussionmentioning
confidence: 99%